If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(4x + -2) = 24 Reorder the terms: ln(-2 + 4x) = 24 (-2 * ln + 4x * ln) = 24 (-2ln + 4lnx) = 24 Solving -2ln + 4lnx = 24 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Reorder the terms: -24 + -2ln + 4lnx = 24 + -24 Combine like terms: 24 + -24 = 0 -24 + -2ln + 4lnx = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-12 + -1ln + 2lnx) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-12 + -1ln + 2lnx)' equal to zero and attempt to solve: Simplifying -12 + -1ln + 2lnx = 0 Solving -12 + -1ln + 2lnx = 0 Move all terms containing l to the left, all other terms to the right. Add '12' to each side of the equation. -12 + -1ln + 12 + 2lnx = 0 + 12 Reorder the terms: -12 + 12 + -1ln + 2lnx = 0 + 12 Combine like terms: -12 + 12 = 0 0 + -1ln + 2lnx = 0 + 12 -1ln + 2lnx = 0 + 12 Combine like terms: 0 + 12 = 12 -1ln + 2lnx = 12 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| x^3=(1/27) | | lnx=13 | | x/3.1=0.4 | | 0=3y^2+10 | | 8x+24=8(x+3) | | x/8=5/16 | | F(n)=-8n+21 | | 3x=-2y+9 | | 14y/9y^2 | | 8x-(3+5x)=3(2x-7) | | 5a+3b=128 | | 5x-3x+4(x-6)=2 | | 11e-4=8+4e+7e | | 2y=13x | | 8x-6+2x=14+5x | | x=2/x-1 | | 0=3x^2+18+27 | | ((6x^(2)-24x)/(2x))/((x^(2)-16)/(7x^2)) | | -4x-9y=27 | | 5/5x-10 | | (x-y)-(-x+y)= | | X/12=36 | | 17d^2-6d=0 | | 4y+14+2y=8y+4 | | (3a-b)-(6a+2b)= | | 4(2x-5)=7(x+2) | | 44=30n | | (x-y)-(x+y)= | | (8m+6n)-(7m-5n)= | | 24=3/4y | | -12x+5y=17 | | x+2.6x=180 |